Condensed 1,4-dihydropyridines with various esters and their calcium channel antagonist activities - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2009)
New alkyl 2,6,6-(2,7,7)-trimethyl-4-(2-fluoro-3-chloro-5-trifluoromethylphenyl)-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylates and 9-(3-chloro-2-fluoro-5-trifluoromethylphenyl)-6,6(7,7)-dimethyl-6,7-dihydrofuro[3,4-b]quinoline-1,8-diones have been synthesised and their calcium antagonistic activities on isolated rabbit sigmoid colon have been investigated and compared with Nifedipine. The investigation examined the influence of ester groups in the 3-position of the HHQ ring and the 2-methoxyethyl analogs were found to be the most active derivatives. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Hexahydroquinoline; Furoquinoline; Calcium antagonistic activity; Biotransformation; NITRIC-OXIDE; SMOOTH-MUSCLE; PHARMACOLOGICAL-ACTIVITIES; IN-VITRO; DERIVATIVES; HEXAHYDROQUINOLINONES; MODULATORS; CELLS